Menjaga Daya Tahan Tubuh dengan Olahraga Saat Pandemi Corona COVID-19 - Furkan, Furkan; Rusdin, Rusdin; Shandi, Shutan Arie (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Since the entry of Covid-19 in Indonesia, people have been asked to stay at home and do everything from home. While at home, maybe many people find it difficult to maintain their health because they cannot exercise outside the home as usual or they are lazing around too much at home.